A historical review of foreign ideology in planning practice in Vietnam - The Anh, Dinh; Baihao, Li; Xiaogeng, Ren (International Planning History Society Proceedings, 2018)
Within 2,000 years, Vietnam was ruled by China for more than 1,000 years, was colonized by France for almost 100 years, and was divided into pro-American and pro-Soviet Union camps for more than 20 years during the world's cold war. It can be stated that Vietnam’s political, social, cultural and other aspects contain deep foreign trails, the same as urban planning. The article reviews some foreign thoughts, their practices and their influences that appeared in the history of Vietnam. With limited historical data and imperfect research foundations, these papers aim to reconstruct a clue about planning characters and planning events. Based on the source of thoughts, this article summarizes the perceived historical information and divides it into four parts: China, France, the Soviet Union and the United States, presenting in chapters while focusing on an important feature of urban planning in Vietnam, which is the superposition of multiple dimensions of urban and rural concepts, construction techniques and concept technology of different cultures in the same physical space dimension. In the conclusion, the article will analyze this feature, explains how it has been formed and what kind of influence and effect it has had on urban planning since 1986 Doi Moi.